"\\frac{dN_1}{dt}=-k_1N_1, \\quad N_1(0)= N_{1,0}"
"\\frac{dN_2}{dt}=-k_2N_2, \\quad N_2(0)= N_{2,0}"
We have the following solutions:
"N_1(t)=N_{1,0}e^{-k_1t}" and "N_2(t)=N_{2,0}e^{-k_2t}"
Suppose that at the time "t=t_0" the population sizes are equal:
"N_1(t_0)=N_2(t_0)"
"N_{1,0}e^{-k_1t_0} =N_{2,0}e^{-k_2t_0}"
"\\frac{N_{1,0}}{N_{2,0}}=e^{(k_1-k_2)t_0}"
"(k_1-k_2)t_0=\\ln(\\frac{N_{1,0}}{N_{2,0}})"
"t_0=\\frac{1}{k_1-k_2} \\ln(\\frac{N_{1,0}}{N_{2,0}})"
Answer: at the time "t_0=\\frac{1}{k_1-k_2} \\ln(\\frac{N_{1,0}}{N_{2,0}})"
Comments
Leave a comment